Kajian Konsep Dasar Sosiologi Muatan IPS Kelas 5 di Sekolah Dasar - Siti Aeti; Purnamasari, Iin (Pena Edukasia, 2024)
According to Auguste Comte and Durkheim, “ Sociology is knowledge Because adopt And apply method scientific . Sociology of course utilise method scientific in learn principal the discussion . By Because That Sociology is knowledge . There are some other people like Max-weber who denied the status of science knowledge compared to Sociology . he said Sociology No Can become Objective science . Sociology is a science that investigates the structures and processes of social life as a whole/system . Sociology is knowledge general knowledge , meaning learn common symptoms every interaction between human, so sociology is categorical social science pure, abstract, effortful look for understanding general, rational, empirical And nature general . Sociology is a science that studies human behavior in society . This science studies human behavior and society in a group that is being built. Examples of these groups are families, ethnic groups, countries, and political organizations. Whereas function from Sociology to provide social data needed at the planning, implementation and assessment stages of development . At the planning stage, the thing that must be considered is social needs. At the implementation stage, what must be seen is the social strength of society and the process of social change , roles sociology in the environment family very important For development participant educate in the future, a meaningful family give birth to capable generation compete in accordance development era , and create moral generation karimah so that capable synergize in the environment family, school public nation and country.